2011
DOI: 10.1002/jcop.20443
|View full text |Cite
|
Sign up to set email alerts
|

Social capital in promoting the psychosocial adjustment of chinese migrant children: interaction across contexts

Abstract: Drawing upon a sample of 772 migrant children and their parents in Shanghai, China, this study investigated how the interactions of social capital embedded in a range of social contexts (i.e., family, school, peer, and community) influenced the psychosocial adjustment of Chinese migrant children. Results of multiple-group structural equation modeling revealed a moderating effect of community social capital on the associations between other dimensions of social capital and child psychosocial adjustment. Family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 46 publications
0
25
1
Order By: Relevance
“…Meltzer et al (2007) found an association between children's perception of neighborhood trustworthiness and safety and their mental health, using data of 3340 11 to 16-year-old children in Great Britain. Some studies in the Chinese context also demonstrated the positive effects of community social capital on the mental health and psychosocial adjustment of migrant children in urban cities (Wu et al, 2011;Wu et al, 2014).…”
Section: Social Capital and Child Mental Healthmentioning
confidence: 94%
“…Meltzer et al (2007) found an association between children's perception of neighborhood trustworthiness and safety and their mental health, using data of 3340 11 to 16-year-old children in Great Britain. Some studies in the Chinese context also demonstrated the positive effects of community social capital on the mental health and psychosocial adjustment of migrant children in urban cities (Wu et al, 2011;Wu et al, 2014).…”
Section: Social Capital and Child Mental Healthmentioning
confidence: 94%
“…Social relationships have acted as strong determinants that contribute to psychosocial wellbeing and academic achievement of migrant children (Dimitrova et al 2014;Wong et al 2009;Wu et al 2011). Murphy (2008) further advocated that migrant children should not been seen as one vulnerable or isolated category, rather as complex social beings who are actively engaged in social interactions with family, teachers and peer groups.…”
Section: Social Relationshipsmentioning
confidence: 98%
“…For example, Kwan (2010) found that compared to local Hong Kong students, teenagers with migrant backgrounds reported significantly lower satisfaction with life. In predicting life satisfaction among Chinese migrant children, an analysis by Wu et al (2011) underscored the interplay of social capital embedded in family, school, community, and peer contexts for promoting psychosocial adjustment.…”
Section: School Satisfactionmentioning
confidence: 98%
“…The second is to investigate factors affecting the maintenance of health of these migrant children, and the processes through which such influence is exerted. Unfortunately, the majority of prior studies within China have simply gathered empirical data as to whether migrant children were healthy or not, as for example recent reports from Shanghai and Guangzhou that migrant children experience lower self-esteem and life satisfaction, and display more symptoms of depression, separation anxiety, generalized anxiety and hostility than their urbanite counterparts (Mao and Zhao 2012;Mou et al2013;Wong et al 2009;Wu et al 2011). Only a limited number of studies have investigated factors or processes involved in health maintenance, such as relationships between social stress, social ties linking migrants to their host cities and rural home communities, and the mental health of migrants and their children (Cheung 2013(Cheung , 2014.…”
Section: Introductionmentioning
confidence: 98%